Modeling talent development pathways in alpine ski racers - Cowan, R. L.; Fawver, B.; Lohse, K. R.; Taylor, T. (Psychology of Sport and Exercise, 2021)
We explore developmental pathways to excellence in sub-elite adolescent alpine ski racing by exploring athletes' engagement in practice activities that characterize sport specialization and/or diversification. Moreover, we extend previous research by using more refined linear mixed-effects models to examine changes in practice and performance data over time rather than relying on the less sensitive repeated measures ANOVAs typically used in previous research. Altogether, 174 individuals (M = 15.9 yrs, women = 91) from professional development academies in the United States completed a sport-specific Practice History Questionnaire (PHQ). We recorded national rankings in technical events to assess performance. Mixed-effects models indicated that hours in ski-related activities generally increased over time (linear ß = 1.38, p's < 0.001), except time spent in play, which decreased over time (ß = 102.8, p = 0.002). Performance rankings also improved over time (ß = 30.99, p < 0.001), with more time spent in ski-activity associated with greater rates of improvement, particularly in younger skiers (ß = 9.77, p's < 0.001). The effects were largely driven by time spent in coach-led group practice (ß = 2.16, p < 0.001). Overall, an earlier age of first engagement was associated with better rankings (ß = -15.40, p = 0.024), and accumulating more hours in other sports was also associated with greater rates of performance improvement (ß = -8.87, p = 0.014). Sub-elite alpine ski racers engage early in the sport, with higher-ranked athletes spending more time in ski-specific practice, particularly group practice, during development. However, these athletes generally continued to participate in other sports across development, providing greater support for the early engagement hypothesis rather than early specialization per se. Highlights: • Using mixed effects models to examine developmental trajectories over time. • Expertise is modulated by engagement activities across development. • Practice activities and performance trends toward expertise development in sport. • Developmental trajectories predict a multifaceted pathway to expertise for sub-elite alpine skiers.